PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAk) - Fahriani, Dian (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
This study aims to analyze and provide empirical evidence about the influence of motivational quality, careermotivation, and economic motivation on student interest in accounting for Education PPAk follow. The resultsare (1) The first hypothesis is accepted because no significant influence on the motivation of the quality ofstudent interest in accounting for education PPAk, (2) The second hypothesis was rejected because there was nosignificant effect of motivation on student interest in accounting careers to follow PPAk education, (3) The thirdhypothesis was rejected because there was no significant effect of the economic motivation for interest in theeducation of accounting students to follow PPAk.Keywords : motivational quality, career motivations, economic motivations, interests follow PPAk education,accounting students